Web-Based Discussion in Teaching and Learning Organic Chemistry: Student’s Conception and Reflection - Iyamuremye, Aloys; Nsabayezu, Ezechiel; Mukiza, Janvier (International Journal of Emerging Technologies in Learning (iJET), 2022)
The current study explores students’ reflection and conception towards the utilization of web-based discussion in teaching and learning organic chemistry. The study seeks to investigate the influence of web-based discussion on students’ performance in teaching and learning organic chemistry. A total of 153 senior three students were involved in the study. A mixed research approach was used to collect data whereby an achievement test was used to collect quantitative data while an open-ended questionnaire was used to collect qualitative data. A paired t-test was used to analyze quantitative data while interpretive analysis was used to analyze qualitative data. The results revealed that a web-based discussion is a powerful tool that enhances students’ performance in organic chemistry (p˂ 0.05, df =152). Students reflect positively on the effectiveness of web-based discussion as it helps them to share knowledge and experience, enhance interaction, confidence, and motivation. Some challenges were also highlighted including insufficient computer, smartphone, and internet connection.